A Journey - Blair, Tony, 1953- (London Hutchinson, 2010)
Tony Blair is a politician who defines our times. His emergence as Labour Party leader in 1994 marked a seismic shift in British politics. Within a few short years, he had transformed his party and rallied the country behind him, becoming prime minister in 1997 with the biggest victory in Labour's history, and bringing to an end eighteen years of Conservative government. He took Labour to a historic three terms in office as Britain's dominant political figure of the last two decades. In this firsthand account, he describes his role in shaping our recent history, from the aftermath of Princess Diana's death to the War on Terror. He explores the challenges of leadership, and the ramifications of standing up, clearly and forcefully, for what one believes in. He also looks ahead, to emerging power relationships and economies, addressing the vital issues and complexities of our global world.--From publisher description.
Include Colour Illustration and Index
Keywords: Blair, Tony, 1953- -- Great Britain -- Politics and government -- Labour Party (Great Britain) -- Prime ministers -- Diplomatic relations -- Politicians -- Ex-prime ministers